Features of electrocardiographic changes in non-coronarogenic syndromes in patients with COVID-19 - E. V. Shlyakhto; E. V. Parmon; E. R. Berngardt; E. S. Zhabina (Российский кардиологический журнал)
The ongoing pandemic caused by virus SARS-CoV-2 encourages the search for ways to save the population. Since people first encountered this disease, it is being actively studied, and updating medical information is extremely valuable. Since people first encountered this disease, it is being actively studied, and updating medical information is extremely valuable. The purpose of this review is to systematize the literature on the effect of SARS-CoV-2 on the cardiovascular system, focusing on changes in the surface electrocardiogram depending on the clinical course of the disease, the characteristics of the treatment and outcomes, and the possible identification of electrocardiographic predictors of complications, as well as sudden cardiac death in patients with non-coronarogenic syndromes with new virus infection (COVID-19).